2023
DOI: 10.3389/fmed.2023.1116489
|View full text |Cite
|
Sign up to set email alerts
|

Rheumatoid arthritis and the risk of end-stage renal disease: A nationwide, population-based study

Abstract: IntroductionDespite the risk of incident chronic kidney disease among the patients with rheumatoid arthritis (RA), the association of RA and the risk of end-stage renal disease (ESRD) has not been clearly elucidated. We aimed to investigate the association of RA and the risk of ESRD.Materials and methodsA total of 929,982 subjects with (n = 154,997) or without (n = 774,985) RA from the National Health Insurance Service (NHIS) database in Koreas (corresponding to the period between 2009 and 2017) were retrospec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…LaTonya J Hickson et al suggested that over time, RA patients are more likely to experience a decline in kidney function than healthy individuals, which may be related to cardiovascular disease [40]. SangHeonSuh et al found that patients with RA had a higher incidence of end-stage renal disease than subjects without RA, and that the risk of end-stage renal disease(ESRD) was higher in relatively young [41].MTX and some DMARDs, the most commonly used drug for the clinical treatment of RA, as mentioned earlier, has been found to have a risk of kidney damage in some studies [42][43][44], but other studies have shown that low-dose MTX (LD-MTX) is safe in mild to moderate CKD. Before the emergence of MTX and targeted biologics, the occurrence rate of CKD in RA patients is quite high, and most RA patients with CKD in recent years are concentrated in Asia, which may be due to the difference in drug selection of DMARDs in Asia and Western countries, which also indicates the great in uence of drugs on the outcome.Daniel H Solomon et al found in a randomized trial conducted in patients without rheumatic disease that the use of LD-MTX was associated with a mild to moderate increase in the risk of skin cancer and gastrointestinal, infectious, pulmonary, and hematological adverse events, while the risk of renal adverse events was decreased [45][46].…”
Section: Discussionmentioning
confidence: 99%
“…LaTonya J Hickson et al suggested that over time, RA patients are more likely to experience a decline in kidney function than healthy individuals, which may be related to cardiovascular disease [40]. SangHeonSuh et al found that patients with RA had a higher incidence of end-stage renal disease than subjects without RA, and that the risk of end-stage renal disease(ESRD) was higher in relatively young [41].MTX and some DMARDs, the most commonly used drug for the clinical treatment of RA, as mentioned earlier, has been found to have a risk of kidney damage in some studies [42][43][44], but other studies have shown that low-dose MTX (LD-MTX) is safe in mild to moderate CKD. Before the emergence of MTX and targeted biologics, the occurrence rate of CKD in RA patients is quite high, and most RA patients with CKD in recent years are concentrated in Asia, which may be due to the difference in drug selection of DMARDs in Asia and Western countries, which also indicates the great in uence of drugs on the outcome.Daniel H Solomon et al found in a randomized trial conducted in patients without rheumatic disease that the use of LD-MTX was associated with a mild to moderate increase in the risk of skin cancer and gastrointestinal, infectious, pulmonary, and hematological adverse events, while the risk of renal adverse events was decreased [45][46].…”
Section: Discussionmentioning
confidence: 99%
“…End-stage renal disease is twice as likely in RA than in non-RA comparators, and the excess in risk is particularly apparent in younger age groups [50]. Improved control of RA with the use of biologics has been associated with decreased likelihood for chronic kidney disease progression in RA in a Japanese cohort [51].…”
Section: Introductionmentioning
confidence: 99%
“…Since different organs of the body are affected by uremia caused by chronic kidney failure, ESRD usually manifests several signs and symptoms, including hypertension, congestive heart failure, pulmonary edema, pericarditis, skin rash, purpura, Kussmaul breathing, uremic pneumonia, ammonia breath, diarrhea, gastrointestinal bleeding, anemia, thrombocytopenia, amenorrhea, testicular atrophy, muscle cramps, and renal osteodystrophy (2)(3)(4)(5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%